SYNTHESIS OF MAGNETITE NANOPARTICLES (Fe3O4) BASED ON TAMAN RIVER SAND MAGNETIC MINERALS - Agung, Gusti Kade Agung Widiantara; Mardana, Ida Bagus Putu; Arjana, I Gede (Indonesian Physical Review, 2024)
This research aims to produce Fe3O4 magnetic nanoparticles-based Taman River sand as the raw material through coprecipitation. The Fe content percentage in the Taman River sand after separation was characterized using XRF testing. The lattice parameters and crystal size of the samples were tested using XRD. The nanoparticles' morphology, structure, particle shape, and elemental content were characterized using SEM-EDX. The magnetic properties and magnetic saturation values were tested using VSM. XRF testing results on the iron sand showed a Fe content of 84.72%. The synthesis resulted in a brNownish-black Fe3O4 nanoparticle powder that a permanent magnet could attract. Based on the XRD results, the Fe3O4 nanoparticle powder peaks were obtained at X-ray diffraction pattern angles of 2θ: 21.44°, 35.38°, 41.74°, 50.78°, 63.36°, 67.70°, and 74.66°, indicating the presence of Fe3O4 nanoparticles. The crystal structure formed was cubic with lattice parameters a = b = c = 8.331 Å and a crystal size of 18.43 nm. SEM-EDX results showed an average particle size of 25-30 nm. VSM results indicated that the Fe3O4 sample had a saturation magnetization (Ms) of 27.36 emu/g, a remanent magnetization (Mr) of -0.01 emu/g, and a coercive field (Hc) of 0.01 T.